'Trust-busting' after JSC Mezhdunarodniy Promyshlenniy Bank v Pugachev & ors [2017] EWHC 2426 (Ch). Issue 2 (18th January 2018) - Akkouh, Tim; Lloyd, Christopher
Abstract: Mezhprom v Pugachev is an important 'trust-busting' decision of the English Chancery Division (Birss J). The Judge held that the true effect of five detailed trust deeds was to create a series of bare trusts for the settlor, though he would (if necessary) also have concluded that the trusts were shams. The decision makes it easier for discretionary trusts settled for asset preservation purposes to be unwound where the settlor retains substantial control over the trust assets; it will, therefore, be welcomed by those acting for claimants in civil fraud actions.